Three essays on audit market development: evidence from China’s recent reforms - Al Natour, Abdul Rahman Ahmad Abdullah (2019)
This thesis examines the impact of China’s market developments on the accounting industry over the period 2003 to 2014. In this period China initiated the Split-share Structure Reform (SSSR) to privatise Local State-owned Enterprises (LSOEs). Moreover, China announced “Document 56” with the aim of developing its domestic accounting industry. The thesis consists of an introductory chapter, an institutional background chapter, three empirical essays, and a concluding chapter.